Oral Pyogenic Granuloma in an 11-year-old Child: A Case Report - Subhani Vaidya; Senchhema Limbu; Parajeeta Dikshit; Manisha Malla (Journal of South Asian Association of Pediatric Dentistry)
Pyogenic granuloma (PG) is the most common inflammatory hyperplasia occurring in the oral cavity that occurs as a reactive or reparative response to factors such as local irritation, physical trauma, food impaction, periodontitis, or hormonal factors. These lesions are seen most frequently among people in the 20s but are not common among children. This paper describes the case of a PG associated with an 11-year-old female patient, with a detailed description of clinical, radiographic, and histopathologic features, and its surgical management by complete excision of the mass.